2019
DOI: 10.1111/gcb.14842
|View full text |Cite
|
Sign up to set email alerts
|

Winter climate change and the poleward range expansion of a tropical invasive tree (Brazilian pepper—Schinus terebinthifolius)

Abstract: Winter climate change is expected to lead to the tropicalization of temperate ecosystems, where tropical species expand poleward in response to a decrease in the intensity and duration of winter temperature extremes (i.e., freeze events). In the southeastern United States, freezing temperatures control the northern range limits of many invasive nonnative species. Here, we examine the influence of freezing temperatures and winter climate change on the northern range limits of an invasive nonnative tree—Schinus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…What are the implications of our findings for mangrove range dynamics due to climate change? In response to warming winter temperature extremes (USGCRP, ), mangroves and other tropical organisms are expected to move northward into more temperate biomes in eastern and central North America (Carter et al, ; Cavanaugh et al, ; Osland et al, ; Osland & Feher, ). In combination with temperature projections and models of mangrove propagule dispersal (Van der Stocken, Carroll, Menemenlis, Simard, & Koedam, ; Van der Stocken, Wee, et al, ), establishment (Krauss et al, ), and growth (Berger et al, ), the temperature thresholds identified for A. germinans leaf damage, mortality and biomass recovery can be used to help scientists and natural resource managers better anticipate mangrove range dynamics in a warming world.…”
Section: Discussionmentioning
confidence: 99%
“…What are the implications of our findings for mangrove range dynamics due to climate change? In response to warming winter temperature extremes (USGCRP, ), mangroves and other tropical organisms are expected to move northward into more temperate biomes in eastern and central North America (Carter et al, ; Cavanaugh et al, ; Osland et al, ; Osland & Feher, ). In combination with temperature projections and models of mangrove propagule dispersal (Van der Stocken, Carroll, Menemenlis, Simard, & Koedam, ; Van der Stocken, Wee, et al, ), establishment (Krauss et al, ), and growth (Berger et al, ), the temperature thresholds identified for A. germinans leaf damage, mortality and biomass recovery can be used to help scientists and natural resource managers better anticipate mangrove range dynamics in a warming world.…”
Section: Discussionmentioning
confidence: 99%
“…Extremes of low temperature (i.e. frost events) can cause dieback (Cavanaugh et al 2014, Matusick et al 2014) and limit the poleward distribution of plants (Cavanaugh et al 2014, 2015, Osland and Feher 2020, Osland et al 2020). Observed declines in frost events have facilitated the expansion of frost sensitive species to cooler climes (Cavanaugh et al 2014) while increases in hot and dry conditions are contributing to plant dieback at regional and global scales (Mitchell et al 2014, Allen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades increasing temperatures have been shown to have an impact on the distribution of species across a wide range of taxonomic groups [ 1 , 2 ]. Depending on the species’ adaptability to a warmer climate and the ability to disperse, species may either (i) increase their distribution range due to conditions becoming more favourable in areas that were previously inhospitable [ 3 , 4 ]; (ii) contract in range as their habitat becomes increasingly unsuitable [ 5 , 6 ]; or (iii) move away from areas that have become unsuitable towards habitats that have become more favourable [ 7 , 8 ]. To date most species appear to expand their natural distribution range, and for the majority of species both a northward [ 9 , 10 ] and an upward [ 11 13 ] range expansion seems to be the most common movement pattern.…”
Section: Introductionmentioning
confidence: 99%